2021
DOI: 10.1111/ejn.15407
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity predicts sequential processing differences in music perception ability

Abstract: To relate individual differences in music perception ability with whole brain white matter connectivity, we scanned a group of 27 individuals with varying degrees of musical training and assessed musical ability in sensory and sequential music perception domains using the Profile of Music Perception Skills‐Short version (PROMS‐S). Sequential processing ability was estimated by combining performance on tasks for Melody, Standard Rhythm, Embedded Rhythm, and Accent subscores while sensory processing ability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Differences in how musical expertise is defined across studies might also underlie some of the contradictory findings reported in the literature. Indeed, the dichotomous categorization of individuals into musicians versus non-musicians may not reflect the complete range of musical abilities within the population (Law et al, 2012;Rajan et al, 2021;Swaminathan & Schellenberg, 2021). Some individuals may have good musical perceptual skills even in the absence of formal musical training (Mankel et al, 2018).…”
Section: Relationship Between Stream Segregation and Speech Perceptio...mentioning
confidence: 99%
“…Differences in how musical expertise is defined across studies might also underlie some of the contradictory findings reported in the literature. Indeed, the dichotomous categorization of individuals into musicians versus non-musicians may not reflect the complete range of musical abilities within the population (Law et al, 2012;Rajan et al, 2021;Swaminathan & Schellenberg, 2021). Some individuals may have good musical perceptual skills even in the absence of formal musical training (Mankel et al, 2018).…”
Section: Relationship Between Stream Segregation and Speech Perceptio...mentioning
confidence: 99%
“…In order to relate performance on production tasks to performance on perceptual tasks we used stimuli from the tempo and rhythm subtests of the Profile of Music Perception Skills (PROMS; Law and Zentner, 2012 ); thus, the name “Tapping-PROMS.” The PROMS exists in several versions that have all been shown to be both valid and reliable ( Law and Zentner, 2012 ; Zentner and Strauss, 2017 ; Zentner and Gingras, 2019 ). Recent evidence includes demonstrations of large differences between musicians and non-musicians on Mini-PROMS test scores (e.g., Bosch et al, 2020 ; Sun et al, 2021 ), as well significant associations of PROMS-S scores with brain activation patterns involved in music processing ( Rajan et al, 2021 ). Using perception and production stimuli from the same test source ensures that perceptual and production skills can be directly related to each other.…”
Section: Challenges In the Development Of Music Aptitude Batteriesmentioning
confidence: 99%
“…The PROMS exists in several versions that have all been shown to be both valid and reliable (Law & Zentner, 2012 ; Zentner & Gingras, 2019 ; Zentner & Strauss, 2017 ). Recent evidence includes demonstrations of large differences between musicians and nonmusicians on Mini-PROMS test scores (e.g., Sun et al, 2021 ; Vanden Bosch der Nederlanden et al, 2020 ), as well significant associations of PROMS-S scores with brain activation patterns involved in music processing (Rajan et al, 2021 ). Table 1 provides an overview of key characteristics of these versions, along with other recently developed musical ability tests.…”
Section: Introductionmentioning
confidence: 99%